Peranan Perhutanan Sosial terhadap Pendapatan Masyarakat (Studi Kasus Proyek Penanaman di Desa Nanasi Kecamatan Poigar Kabupaten Bolaang Mongondow) - Gabby Y. Rondonuwu; Hengki D. Walangitan; Maria Y.M.A. Sumakud (Universitas Sam Ratulangi, 2022)
ABSTRACT The aims of this study was to describe the role of forestry projects in this case the planting project in the context of forest rehabilitation in Nanasi Village, Poigar sub-district, Bolaang Mongondow Regency. The role of the project is evaluated based on the aspect of involvement as well as the amount of direct income received by the community participating in the project. This study uses an interview method with an open questionnaire model. Determination of respondents using purposive sampling technique with the number of respondents as many as 15 people. Furthermore, to analyze community involvement and the amount of income earned by project participants using descriptive analysis. The results showed that from the implementation of the project in the field, not everything went according to the technical design, but there were changes and adjustments according to the conditions in the field such as the land area in the technical design was 25 Ha and in practice the land area used was 27 Ha, fertilizer was not used for planting. cage/compost and maintenance for the second year is not carried out. The direct involvement of the community in this project as labor in the activities of transporting seeds to the planting site, preparing the planting area, followed by planting and maintaining plants. The results of the analysis obtained that the direct transfer value through work wages to the participating communities was Rp. 2,500,000 for 26 working days. The results of the interview obtained information that the income obtained through the investment project was used as business capital, school fees, living expenses and also as a cost to cover urgent needs. Keyword: social forestry, income, planting projects